Exogenous P compounds differentially interacted with N availability to regulate enzymatic activities in a meadow steppe. (25th November 2019) - Wang, Ruzhen; Cao, Yanzhuo; Wang, Hongyi; Dijkstra, Feike A.; Jiang, Jinglun; Zhao, Ruonan; Ma, Wang; Li, Tianpeng; Dorodnikov, Maxim; Wang, Zhengwen; Sardans, Jordi; Peñuelas, Josep
Abstract: Increased inputs of ecosystem nitrogen (N) and phosphorus (P) may affect the activity of soil enzymes that play essential roles in the metabolization of carbon (C), N and P for microbial growth. However, the associations between soil enzymatic activities and N and P availability remain poorly understood. We conducted a study in a meadow steppe to elucidate the effects of the addition of N, as ammonium nitrate (NH4 NO3 ), and two forms of P with contrasting solubility, comprising monopotassium phosphate (KH2 PO4 ) and the less soluble triple superphosphate (Ca(H2 PO4 )2, on activity of β‐glucosidase (BG), N ‐acetyl‐glucosaminidase (NAG) and acid and alkaline phosphomonoesterases (PMEs). In general, there was a positive effect of N on BG, NAG and alkaline PME activity as a result of enhanced soil N availability, plant–microbe nutrient competition and plant P uptake. Addition of KH2 PO4 increased activity of BG, NAG and alkaline PME, but had no impact on acid PME activity. Addition of Ca(H2 PO4 )2 increased NAG activity, but only increased activity of BG and alkaline PME with the addition of N. Concentration of soil available P and microbial biomass P increased with added P, particularly KH2 PO4 . These results provide the first evidence for the N‐ and P‐mediated stimulation of microbial activity depending on the chemical form of added P in this ecosystem. Relationships between activity of BG and NAG, and between that of NAG and PME, were allometric, indicating disproportionate changes in activity of these soil enzymes. This further suggests shifts in microbial acquisition of C, N and P along with increases in availability of N and P that may potentially affect plant productivity. We conclude that scenarios of global environmental change, in which ecosystem availability of N and P is affected, may result in variable activity responses among soil enzymes, and the chemical form of P input should be considered as an important factor influencing meadow steppe grassland ecosystem function. Highlights: Chemical N and P increased enzyme activity but effects varied with P form and rate. N addition promoted soil enzyme activity through enhanced plant–microbe interactions. N availability mediated positive enzymatic responses to P addition. Enzymatic stoichiometry indicated disproportionate changes in microbial C, N and P acquisition.